2020
DOI: 10.31234/osf.io/futpk
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Attitudes toward COVID-19 among Young Adults: Role of Psychological Distress

Abstract: Young adults’ attitudes toward COVID-19 are vital for their adherence to control measures taken by the government to break the chain of contamination. This study aims to measure differences in attitudes to this pandemic across various demographic groups of young adults living inside and outside of Dhaka. The predictors of optimistic attitudes toward COVID-19 also have been investigated. The study is cross-sectional in nature using data from the members of Secondary and Intermediate Level Students’ Welfare Asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 31 publications
1
5
0
1
Order By: Relevance
“…Most of the respondents in this study had positive attitudes toward COVID-19. The respondents who had more knowledge of COVID-19 had less negative attitudes toward COVID-19, which is the findings of other studies 2 , 5 , 21 , 32 . This finding thus supported the hypothesis that more knowledge is associated with less negative attitudes toward COVID-19.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Most of the respondents in this study had positive attitudes toward COVID-19. The respondents who had more knowledge of COVID-19 had less negative attitudes toward COVID-19, which is the findings of other studies 2 , 5 , 21 , 32 . This finding thus supported the hypothesis that more knowledge is associated with less negative attitudes toward COVID-19.…”
Section: Discussionsupporting
confidence: 87%
“…However, despite the importance of researching knowledge, attitudes, and preventive behavioral practices (KAP) toward COVID-19, very few studies 2 , 15 , 16 have been conducted in Bangladesh with a robust methodology and analytical framework. Most of the studies conducted in Bangladesh on KAP toward COVID-19 are of small sample size 17 , 18 , 19 , 20 , non-robust statistical analysis 17 , 18 , with a specific population group and geographic location 17 , 18 , 20 , 21 . On top of that, these studies were conducted in the early periods of detecting the first COVID-19 case in Bangladesh when people were possibly less aware of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Attitudes: From our bibliographic research, we found that even if attitudes towards COVID-19 were optimistic (e.g., the likelihood of being infected was perceived as low), most of the participants took precautionary measures to prevent infection: 96.4% of the participants avoided crowded places and 98% wore masks [34]. In particular, in young adults an optimistic attitude was associated with less psychological distress; also the diffusion of accurate information and a mental health intervention could lead to better attitudes [35]. On the contrary, higher levels of fatalism toward COVID-19 were associated with lower behavioral intentions to support mitigation efforts [36]; also those who believed that the fear of COVID-19 caused unnecessary absences from work and schools, reported higher levels of anxiety [37].…”
Section: Results For Beliefs and Media Persuasionmentioning
confidence: 79%
“…This finding is lower than studies conducted in northern Ethiopia (85.3%) [27], University of Dhaka (43.4%) [32], Jilin Province, China (40.4%) [33], 194 cities in China (53.8%) [34]. The outbreak of COVID-19 has shown many psychological problems [35] that need provision of improved psychological interventions at national, regional, and district levels.…”
Section: Discussionmentioning
confidence: 75%